Curating Hybrid-Style University Experiences: Framework Development for Student Social Connectedness Using Interaction Design and Placemaking - Theresa Wheele; Carmel Lindkvist; Tore Haugen; Clara Weber; Lukas Windlinger (Education Sciences, 2024)
Communication technologies offer new opportunities for building and maintaining social connections at university. However, these technologies need to be better understood for their influence on student experiences in hybrid-style classrooms and guided more effectively. This study identified qualities of social connection to understand how students built/maintained social connection. The study was conducted over two autumn semesters in three hybrid-style classes in Switzerland and Norway. Qualitative methods included observations, interviews, and auto-photography. Approximately 150 h of observational data were gained, including auto-photography of 17 students’ physical online learning spaces, and four interviews with class lecturers. The findings indicated that informal/private spaces, crucial for building/maintaining social connection, were hard to access in hybrid-style learning environments. Communication cultures and social structures offered limited support for accessing these spaces for building/maintaining social connection. Addressing this issue required a processual effort across user-levels to support social connection within a hybrid-style university culture. This effort involved opening access to informal/private spaces by applying the concept of affective atmospheres within placemaking and interaction-design theories. A dimensions of affect framework is developed to help curate learning environments towards social connection. For university campus development, addressing these people–place relations with communication technology could foster technology more effectively to support connection.